Hominin distribution in glacial-interglacial environmental changes in the Qinling Mountains range, central China. (15th October 2018) - Sun, Xuefeng; Lu, Huayu; Wang, Shejiang; Xu, Xinghua; Zeng, Qingxuan; Lu, Xuehe; Lu, Chengqiu; Zhang, Wenchao; Zhang, Xiaojian; Dennell, Robin
Abstract: The Qinling Mountain Range (QMR) in central China encompasses innumerable Paleolithic sites. The hominin settlement in the QMR is comparable with that in the Nihewan Basin in northern China. The recorded information on the loess deposition in the QMR include both hominin remains and environmental changes. Since 2004, geological, geomorphological, archaeological, and chronological investigations were conducted by our team. By systematically using luminescence, paleomagnetic, and 26 Al/ 10 Be burial dating methods to obtain age controls, and by correlating the pedostratigraphy and magnetic susceptibility of the Luochuan loess section, we established the loess–paleosol sequence and chronology of the lithic artifact levels for 35 Paleolithic sites and spots in the QMR. This work remarkable found shifts from glacial-to interglacial-driving hominin settlement patterns. During the stage between 1.2 and 0.7 Ma, large drying events, such as L15 (MIS 38) and L9 (MIS 22, 23 and 24), may have driven hominin migrations when the Loess Plateau was depopulated; moreover, the southern QMR was a glacial refugium. During the stage after ∼0.60 Ma, the contrasts between glacial and interglacial scales are the greatest; furthermore, longer and warmer humid interglacial environments were dominant. S5 (MIS 13, 14, 15) and S1 (MIS 5) interglacial periods provided the optimal environments for hominin settlement and dispersal. On the basis of investigations, we also found that the hominin settlement is relatively continuous from ∼1.20 Ma to ∼0.05 Ma in the QMR. The human occupation of the QMR decreased considerably after ∼0.05 Ma, probably because of changes in climate and human adaptations. Highlights: We had dated 35 Paleolithic sites and the spot in the Qinling Mountain Range in central China. We investigated how hominin groups responded to glacial–interglacial shifts from ∼1.20 Ma to ∼0.05 Ma. The drastic decline of human occupation after ∼0.05 Ma can be linked to the decline in Gross primary productivity.